MEMBANGUN KEBERLANJUTAN USAHA BERBASIS ECO FRIENDLY PADA USAHA COCOLOCO BALI, DESA AYUNAN, KABUPATEN BADUNG - Lestari, Ni Luh Putu Ratna Wahyu; IA Cynthia Saisaria Mandasari; I Gusti Ngurah Sugiana (Synergy and Society Service, 2024)
CocoLoco Bali under the auspices of CV. Puspa Bawartha, located in Ayunan Village, Banjar, Central Badung, is a business engaged in the field of young coconut suppliers in attractive packaging and ready to consume, which will later be distributed directly to consumers who order. Mr. Biki's business is an eco-friendly product business, where this business produces environmentally friendly products and has minimal impact on the environment. This eco-friendly product business has very good prospects, considering that Bali is a tourism area. The number of investors who build hotels, restaurants, and beach clubs is a great opportunity for CocoLoco to increase sales. However, increasing sales will certainly affect the increase in waste generated from peeling coconuts. The next problem is related to employee health and safety (K3). In the production process, employees will use very sharp machines to peel coconuts, as well as very hot tools for the labeling process. The Community Partnership Empowerment Program (PKM) implemented at CV. Puspa Bawartha "CocoLoco Bali" has provided various positive impacts both from a social and economic perspective.